Penerapan Metode Waterfall pada Sistem E-Order Makanan dan Minuman Berbasis Web dan Mobile - Nugroho, Bagus Candra; Wibowo, Adityo Permana (Journal of Information System Research (JOSH), 2024)
Warung Sate Ojolali is a restaurant that sells various food menus, especially satay, located in Kebasen District, Banyumas Regency, Central Java. In the era of increasingly fierce culinary business competition, many restaurants and cafes have sprung up which requires companies to implement effective strategies to attract more visitors. In this study, a problem was found in the management of a culinary business where a business that has many transactions with customers, but these activities are hampered because the details of the food and beverage menu offered by the restaurant are less informative such as offers that are less detailed regarding the available menus and the delivery of menu books as ordering media that are less complete or updated. Therefore, researchers designed the development of a Web and Mobile Based Food and Beverage Ordering System. This system is designed using the Waterfall method which aims to simplify the ordering process for customers. This Android-based ordering application allows customers to order the desired menu in detail through an intuitive interface. Integration with the internet network makes the ordering experience more efficient, without the need to come directly to the location. The results of the research obtained while in the form of an online food and beverage ordering system that can run according to its function where the admin can add, edit and can delete the menu data provided. In addition, the process of recording orders that were previously done manually can be done automatically by the system so that an admin only needs to recap order data to carry out the transaction process. The implementation of this system not only improves operational efficiency, but also simplifies management, expands market reach, and improves user experience. Thus, this innovation is expected to support business growth and significantly increase customer satisfaction.